α4βδ GABA(A) receptors trigger synaptic pruning and reduce dendritic length of female mouse CA3 hippocampal pyramidal cells at puberty - Parato, Julie (Neuroscience, 2018)
Synaptic pruning during adolescence is critical for optimal cognition. The CA3 hippocampus contains unique spine types and plays a pivotal role in pattern separation and seizure generation, where sex differences exist, but adolescent pruning has only been studied in the male. Thus, for the present study we assessed pruning of specific spine types in the CA3 hippocampus during adolescence and investigated a possible mechanism in the female mouse. To this end, we used Golgi-impregnated brains from pubertal (~PND 35, assessed by vaginal opening) and post-pubertal (PND 56) mice. Spine density was assessed from z-stack (0.1μm steps) images taken using a Nikon DS-U3 camera through a Nikon Eclipse Ci-L microscope and analyzed with NIS Elements. Spine density decreased significantly (P<0.05) during adolescence, with 50–60% decreases in mushroom and stubby spine-types (P<0.05, ~PND35 vs. PND56) in non-proestrous mice. This was associated with decreases in Kalirin-7, a spine protein which stabilizes the cytoskeleton and is required for spine maintenance. Because our previous findings suggest that pubertal increases in α4βδ GABAA receptors (GABARs) trigger pruning in CA1, we investigated their role in CA3. α4 expression in CA3 hippocampus increased 4-fold at puberty (P<0.05), assessed by immunostaining and verified electrophysiologically by an increased response to gaboxadol (100nM), which is selective for α4βδ. Knock-out of α4 prevented the pubertal decrease in Kalirin-7 and synaptic pruning and also increased the dendritic length, demonstrating a functional link. These data suggest that pubertal α4βδ GABARs alter dendritic morphology and trigger pruning in female CA3 hippocampus.